PENGARUH FATHERLESS DENGAN REGULASI EMOSI TERHADAP RESILIENSI AKADEMIK SISWA SMK PGRI 2 KEDIRI - Dwi Astari Jarman; H. Hamam H. Hamam; Nasrul Syarif (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
Adolescence is a crucial transitional period in individual development marked by identity exploration, the pursuit of independence, and increased academic demands. In the context of secondary education, students face various pressures from both family and school environments. One key factor in overcoming these challenges is the individual’s ability to adapt psychologically and academically, also known as academic resilience. The presence of a father figure in a child's life and the ability to regulate emotions are two essential aspects that may influence students’ academic resilience. This research employed a quantitative approach using an ex post facto design. The population consisted of grade X and XI students at SMK PGRI 2 Kediri, and the sampling technique used was total sampling, involving 67 respondents. Data analysis was conducted using multiple linear regression with the aid of SPSS software. The results showed that fatherlessness had no significant effect on academic resilience (sig. = 0.219 > 0.05). In contrast, emotion regulation had a significant effect on academic resilience (sig. = 0.000 < 0.05). Simultaneously, fatherlessness and emotion regulation had a significant effect on academic resilience (sig. = 0.000 < 0.05) with a coefficient of determination of 38.4%. These findings indicate that emotion regulation is a dominant factor in building academic resilience among students, even in the absence of a father figure.